Exploratory evaluation of baseline cognition as a predictor of perceived benefit in a study of behavioral therapy for urinary incontinence in Parkinson disease. Issue 3 (19th February 2022) - Chang, Phat L.; Goldstein, Felicia C.; Burgio, Kathryn L.; Juncos, Jorge L.; McGwin, Gerald; Muirhead, Lisa; Markland, Alayne D.; Johnson, Theodore M.; Vaughan, Camille P.
Abstract: Aims: While behavior‐based pelvic floor muscle exercise therapy is an effective treatment for overactive bladder in Parkinson's disease (PD) patients, cognitive function may be a predictor of rehabilitation outcomes. Methods: In a planned exploratory analysis, participants who had a Montreal Cognitive Assessment (MoCA) with a score ≥18 who were randomized in a clinical trial to behavioral treatment were classified by perceived improvement ( Benefit vs. No Benefit ) as reported on a validated Satisfaction and Benefit Questionnaire. General cognition (MoCA), motor procedural learning (Serial reaction time task), verbal memory (Buschke delayed recall), spatial memory (Nonverbal/Spatial selective reminding test), and working memory (Wisconsin card sorting task) were compared between the two groups using Wilcoxon rank‐sum test. Results: Of the 26 participants randomized to behavioral treatment (70% male, mean age 71 ± 6.1 years), 22 participants (85%) reported Benefit and four reported No Benefit . General cognition, motor procedural learning, verbal memory, spatial memory, and working memory did not differ between these groups. While the difference between the time to complete the final practiced series and the random series of the Serial Reaction Time Task (SRTT) was statistically similar between the groups, the Benefit group performed the random sequence more quickly (567.0 ± 136.5 ms) compared to the No Benefit group (959.4 ± 443.0 ms; p = 0.03) and trended toward faster performance in the final practiced series. Conclusions: Perceived benefit from behavioral treatment for overactive bladder was not associated with measures of baseline cognition other than faster completion of the SRTT. This is noteworthy because many behavior‐based therapy studies exclude participants with mild cognitive impairment. Additional studies may evaluate if domain‐specific cognitive function, particularly the assessment of implicit memory, could lead to individualized behavioral therapy recommendations.